Wireless Electrical Stimulators and Sensors Network for Closed Loop Control in Rehabilitation - Andreu, David; Sijobert, Benoît; Toussaint, Mickael; Fattal, Charles; Azevedo-Coste, Christine; Guiraud, David (Frontiers in Neuroscience, 2020)
This paper presents a wireless distributed Functional Electrical Stimulation (FES) architecture. It is based on a set of, potentially heterogeneous, distributed stimulation and measurement units managed by a wearable controller. Through a proof-of-concept application, the characterization of the wireless network performances was assessed to check the adequacy of this solution with open-loop and closed-loop control requirements. We show the guaranteed time performances over the network through the control of quadriceps and hamstrings stimulation parameters based on the monitoring of the knee joint angle. Our solution intends to be a tool for researchers and therapists to develop closed-loop control algorithms and strategies for rehabilitation, allowing the design of wearable systems for a daily use context.